Educational Leadership and Change : An International Perspective - Wong, Kam-Cheung; Cheng, Kai Ming (Book collections on Project MUSE., 1995)
The papers selected cover the shifting role of school leaders and their preparation; the latest trend in management of devolving administrative responsibilities to schools; and the cultural dimension of educational administration. Drawing on experiences from different parts of the world, this volume explores the above issues and reflects the differences in practice.